Management of Regional Assets at the Regional Finance and Asset Agency Office of North Minahasa Regency - Motulo, Kevin K.; Masengi, Evi E.; Wawointana, Thelma (International Journal of Information Technology and Education, 2025)
Efficient administration of Regional Government Assets (RGA) underpins transparent, accountable, and effective local governance. This study examines the implementation of asset administration—specifically bookkeeping, inventory, and reporting—at the Regional Finance and Asset Agency (BKAD) of North Minahasa Regency. Employing a descriptive qualitative approach, data were collected through in-depth interviews with key informants (asset managers, heads of asset divisions), supporting officers, direct observation of work processes, and document analysis (e.g., inventory lists, financial reports, legal regulations). Findings reveal that while BKAD has largely adhered to Minister of Home Affairs Regulation No. 19/2016 on RGA administration, practical challenges persist: delays in data submission by subordinate units, inadequate asset labeling, and reconciliation discrepancies between OPD (Organizational Units) records and BKAD’s central database. The inventory process, conducted annually for high‐value items and quinquennially for other assets, functions satisfactorily but demands enhanced data accuracy and broader utilization of the E-BMD electronic system. To bolster RGA administration, the study recommends strengthening human resource capacity through targeted training, optimizing inter-unit coordination mechanisms, and advancing an integrated asset information system for real-time data capture and validation.